Prognostic tools to assess candidacy for and efficacy of antibody‐removal therapy. Issue 2 (23rd August 2018) - Pinelli, David F.; Zachary, Andrea A.; Friedewald, John J.; Gjertson, David W.; Evans, Michelle A.; Chatroop, Erik N.; Leffell, Mary S.; Vo, Ashley A.; Jordan, Stanley C.; Montgomery, Robert A.; Tambur, Anat R.
Abstract : Currently, the ability to predict or monitor the efficacy of HLA antibody–removal therapies is deficient. We previously reported that titration studies are a consistent and accurate means of assessing antibody strength. To test whether titration studies can also predict which patients are better candidates for desensitization, we studied 38 patients from 3 centers (29 receiving plasmapheresis/low‐dose intravenous immunoglobulin [IVIg]; 9 patients receiving high‐dose IVIg). For patients undergoing plasmapheresis/low‐dose IVIg, antibody titer reduction correlated with number of treatment cycles for both class I and II antibodies but only up to approximately 4 cycles. Reduction in titer slowed with additional cycles, suggesting a limit to the efficacy of this approach. Furthermore, initial titer (predesensitization) can guide the selection of candidates for successful antibody‐removal treatment. In our experience, patients with antibodies at an initial titer >1:512 could not be reduced to the goal of a negative lymphocyte crossmatch, corresponding to a 1:16 titer, despite a significant increase in the number of treatment cycles. Change in mean fluorescence intensity (MFI) value did not correlate with success of treatment if initial MFI values were >10 000, likely due to single antigen bead saturation. Overall, we present a potential prognostic tool to predict candidacy and a monitoring tool to assess efficacy of desensitization treatment. Abstract : Titration of serum during human leukocyte antigen antibody testing predicts suitable candidates for pretransplant desensitization and estimation of the number of cycles of plasmapheresis and intravenous immunoglobulin required.